Characterization, thermal behavior, and electrical measurements of poly[4-(2-bromoisobutyroyl methyl)styrene] - Biryan, Fatih; Demirelli, Kadir (Wiley, 2018)
The 4-(2-bromoisobutyroyl methyl)styrene [BBMS] monomer was synthesized. The homopolymer of BBMS was prepared by free radical polymerization method. The decomposition behavior of P(BBMS) was thermally investigated by thermogravimetric analysis (TGA). For thermal decomposition kinetics of poly(BBMS), Flynn-Wall-Ozawa method was applied to thermogravimetry curves. The first step, which is one of the two decomposition stages, is comprehensively related to elimination of hydrogen bromide and the other step is related to a multi-step process. The activation energy (E-a) of thermal decomposition of the first step and 50% weight loss is 148.5 and 190.7 kJ/mol, respectively. The results showed that the side group elimination without chain breaking comprehensively proceeded at lower temperature, and at progressive temperatures subsequently the specific chain scission did so. Degradation of poly(BBMS) did not lead to depolymerization. H-1, C-13-NMR, and FT-IR analyses showed that the decomposition products during degradation of poly(BBMS) to 260 degrees C were comprehensively HBr and methacrylic acid. Electrically conducting graphene-based poly(BBMS) composites were prepared. The DC and AC electrical measurements of graphene-based poly(BBMS) composites were carried out. The AC dielectric measurements of poly(BBMS) were investigated up to 70 degrees C between 100 Hz and 20 kHz depending on the alternating current conductivities. The dipolar functional groups (C-O, C=O, and Br) of the BBMS segment possesses significantly affect the dielectric constant. Also, the activation energy profile of different graphene/poly(BBMS) composites were revealed by measuring DC conductivity of individual composite material.
Keywords: characterization; electrical properties; poly(BBMS); thermal behavior